Rapidly improving acute myocarditis after a scorpion sting - Nermin Bayar; Selçuk Küçükseymen; İsa Öner Yüksel; Şakir Arslan (KARE Publishing, 2013)
Scorpion stings are usually benign, but especially cardiovascular death has been reported due to complications. Local reactions at the site of the sting as well as organ dysfunction may be due to the effects of a systemic toxin. As a result of the toxic effects of the scorpion toxin on the cardiovascular system, hypertension, arrhythmia, myocarditis, acute heart failure, and pulmonary edema may occur. In this report, we present a 49-year-old male patient who was admitted to our hospital with acute pulmonary edema and respiratory distress following scorpion sting at the wrist. In this case, detection of diffuse left ventricular systolic dysfunction on presentation, immediate improvement with medical treatment, and increased troponin levels in the absence of critical stenosis on coronary angiography suggest the diagnosis of acute myocarditis associated with scorpion bite.